Work Stress of Women Employees in The Information Technology Industry: An Empirical Study with Reference To Chennai City - Malathi, Dr.T.; Srilatha , B. Venkata (International Journal of Accounting and Economics Studies, 2025)
The purpose of the study is to investigate the stress of women employees working in the information technology industry, specifically in Chennai. The (IT) Information Technology business in India has benefited greatly from the country's economic globalization. Information technology is a vital component of the twenty-first century's technology-driven knowledge economy. India is known as a knowledge economy around the world due to its amazing IT industry. IT professionals are constantly under pressure to work effectively because IT services must be cost-effective for the firms that provide them. Work stress is higher in IT organizations than in other types of organizations. Working women in the IT industries have a different set of problems involving both their family and professional lives, thus finding difficulties in balancing work-life. Women must play their roles as a wife, a mother, and an earner. Sometimes women employees in IT organizations are not able to cope with the drastic new technological changes, work nature, intention, attainments, night shift, over workload, etc., and they have been facing heavy work stress. Hence, this study has been conducted to examine work stress factors of women employees such as Over Work Load (OWL), Work Life Imbalance (WLiB), Work Target (WT) and Job Insecurity (JiS) playing havoc in the physical and mental wellbeing, thus creating hurdles to the job performance of women employees in IT industry by taking the sample population from Chennai City. The sample population for the study is 100 women employees drawn from some IT Companies located in the IT parks in Chennai. Percentage Analysis, t-test, test and One-Way ANOVA have been applied for the examination of data collected from the respondents